ROLE OF WOMEN FOR ECONOMIC RESILIENCE - Awaliyah, Dian Nafiatul (UI Scholars Hub, 2022)
Fatayat NU (Nahdlatul Ulama) and Muslimat NU are grassroots community organizations with millions of members throughout Indonesia. They are women and mothers who support their families in education and even the economy. From observations and searches and excavations, it is found that the phenomenon is that they are the ones who continue to drive the family economy during the pandemic when husbands and fathers lose their jobs due to PPKM regulations and also mass dismissals in many companies and other institutions. In addition, many husbands and fathers have died due to Covid-19 and comorbidities. Their economic resilience needs to be supported and encouraged to continue to develop even more in order to improve their welfare and that of future generations. Their economic model that utilizes the existing environment and availability as well as social capital of mutual assistance between members whose culture has been created for a long time can become a pattern that is developed, modified, and expanded its reach for other communities.